Workplace Surveillance of Employees from the Czech Perspective - Štěpánková, Kateřina (Central European Academy Law Review, 2025)
This contribution focuses on workplace surveillance from the Czech perspective. Its basis is to present the essence of surveillance by employers in the Czech Republic – a much-discussed topic influenced by a number of facts such as the development of modern technologies, also included in this paper. These issues are presented from several perspectives – specifically: employees under video surveillance; monitoring of employees’ computers; and consumption of alcohol or other addictive substances under surveillance. In the case of video monitoring, the aspect of GDPR legislation and the Labour Code are discussed in detail. The national attitude towards hidden monitoring and dummy camera systems is also emphasised. For example, it is important that - according to some opinions - the employer is obliged to directly inform the employees about the scope and methods of the employee surveillance in advance. This would completely eliminate employee surveillance carried out with hidden cameras. However, this approach would basically be much harder on employers than the European Court of Human Rights’ case-law. This paper, therefore, represents a different way of interpreting the relevant Czech Labour Code. The role of the Czech Personal Data Protection Office is also highlighted. The development of the opinion of this Office on employee email surveillance is also included. In relation to the topic of employee surveillance through a work computer, the paper also summarises the basic limits that the employer must take into account. Finally, monitoring work premises for the presence of alcohol is a highly important topic as well, with employees forbidden from working under the influence of alcohol. However, the employee surveillance faces some major restrictions in this respect, not only from Czech Labour Code legislation but also by the case-law of the Supreme Court of the Czech Republic.